A Study of educational robotics in elementary schools - Costa, Manuel F. M. (2008)
Every teacher aims to find new pedagogical tools that motivate the students and that are ultimately effective in the teaching/learning process of a broad set of contents. Frequently, novel educational tools are developed that bring new sheds of hope to teachers, parents and students. Some of them are able to survive in the fierce competition, but most disappear in a short span of time. The Information and Communication Technologies (ICT), as a whole, have offered lots of promises to education, and some even talk about a huge revolution. Nowadays, it is certain that its impact on the classrooms is still far from these promises, mainly in what regards elementary education. But, it is undeniable that nowadays there are already a number of tools that can be used by teachers and students. The question is shifting from “Will we use ICT in education?” to “How can we use ICT in education to obtain good results?” In this context, Educational Robotics (ER), the research field that studies the application of Robotics as a pedagogical tool, has been growing in importance in the last few years as an emergent approach to Education. This development has been made possible by the technological advances in ICT and electronics, as well as by the progressive drop of costs.